Evaluation of the Physical-aqueous Properties of Agricultural Soils in the 3rd Sector of the Lower Euphrates Basin – Syria - حايك, شريف; راعي, كنان (Latakia University Journal -Engineering Sciences Series, 2021)
The third sector is located on the right bank of the Euphrates River southeast of town Deir-Alzour, and its square 317 km2, it is bounded on the northeast by the Euphrates River, and on the southwest by a cliff of Paleogene rocks. This research aims to evaluate the important Physical-aqueous properties of agricultural soils in the 3rd Sector of the Lower Euphrates Basin: soil texture; bulk density; real density; porosity; constructional composition; retention capacity; moisture of soil; maximum hygroscopic moisture of the soil and wilting point. The soils of the sector are clayey sand, sandy, and sandy clay, and it has high bulk density in surface horizons and is low in the upper part of subsurface soil, while the real density is increasing with increased depth, its retention capacity ranges between (20-30)% of the volume of soil. There is a relationship between hygroscopic moisture of soils and its structural composition. The research recommends establish an integrated management system for soil, and integrating soil sensing technology and digital morphological scales into future studies and researches.